FOOD ATSID FEEDING HABITS OF THE SNAPPER, LUTIANUS KASMIRA (FORSKAL) FROM THE ANDAMAN SEA - Rangarajan, K (Indian Journal of Fisheries, 2011)
The paper deals with the food and feeding habits of the snapper, Lutianus kasmira(Forskal), a common lutianid fish around Andaman Islands. Teleost fishes, juvenilecrabs and megalopa, and young prawns constituted the chief items of the diet of the fishin that order. Isopods, amphipods, ostracods, polychaetes, stomatopods, asteroids,ophiuroids, gastropods, holothurians, hermit crabs, pteropods, lucifers, caprellids andcypris contributed an insignificant percentage to the diet. The major items of the dietof the fish did not differ significantly from year to year. No marked change in the dietof the fish as it grew from yoting to adult was noticed. Generally active feeding wasnoticed during April to October with a peak during April to August and a poor feedingdtiring the rest of the period. The available data suggest a slackness in feeding dui'ing thespawning season and an active feeding after spawning. Small-sized food organismswere swallowed whole, while large-sized organisms were bitten and swallowed.L. kasmira is essentially a column feeder occasionally resortng to feeding at the boottom.